Language, identity, and translation in J. M. Synge’s The Playboy of the Western World - Chang, Hawk (Penerbit Universiti Kebangsaan Malaysia, 2022)
John Millington Synge’s play The Playboy of the Western World features the playwright’s adoption of Hiberno-English, a mixture of English and Irish, to highlight a peculiar Irish identity. This unique language feature, simultaneously similar to and different from Standard English, marks the playwright’s resistance to British colonization and his Irish cultural identity. By reading Synge’s The Playboy of the Western World, the translated versions of the play from English to Chinese, and translation theories by Eugene Nida and Walter Benjamin, this paper discusses Synge’s Irish identity via the lens of language and translation. It was found that the use of language in The Playboy and the Western World signals Synge’s strong sense of indigenous language and the emphasis on highlighting one’s language awareness and cultural identity. This inextricably linked relationship between language and identity is evidenced by Synge’s play and reinforced by Perng’s and Chang’s Chinese translations.